Implementation of East Lombok Flourishing Program (Renternir Through Interest Free Credit) at MSMEs - Tiara, Ade; Juani, Muhammad; Mispandi, Mispandi (JMET: Journal of Management Entrepreneurship and Tourism, 2024)
Implementation is the process of putting a plan, decision, or policy into action. Implementation also includes a number of actions, such as planning, preparing resources, organizing leadership, and implementing an action or decision. This research aims to find out how the implementation of the Lotim Program improves the development of MSMES  in the Selong district and what obstacles there are to its implementation. The research used in this study is descriptive research with a qualitative approach. The data submitted is then analyzed by reducing the data, presenting the data, and drawing conclusions. The research is based on the theory of Edward III, who uses four factors as a reference for the research: resource, communication, bureaucracy, and attitude. The results of the research implementation of the Lotim development program at MSMES  in the Selong district showed that the implementation of this Lotim development program has been sufficiently good but not fully successful. The recipients of this Growth Lotim program feel that it has been very helpful in developing their venture. The obstacles to the implementation of this program are more likely than the people who are difficult to gather, and the communication and monitoring carried out by the program implementing authorities have not been performed optimally. In this case, the monitoring is performed after the people are declared to accept the Lombok Timur Developing Program.